Using a Local Culture-Based Outdoor Learning Environment to Stimulate Children's Gross Motor Skills at TK Desa Ranggo Dompu - Reniyansyah, Reniyansyah; Ihlas, Ihlas; Muslim, Muslim; Hermansyah, Hermansyah (Journal of Basic Education Research, 2025)
Purpose of the study: The outdoor learning environment is designed to improve children's gross motor skills at TK Desa Ranggo Dompu. The purpose of this study is to describe how the use of outdoor learning environment based on Dompu local culture in improving children's gross motor skills at TK Desa Ranggo Dompu. Methodology: The type of research used is field research with a descriptive qualitative approach. The subjects in this study were the principal, teachers and students of Ranggo Village Kindergarten. Data collection techniques used by observation, interviews and documentation, with data validity testing using data triangulation techniques. Main Findings: The results showed that the local culture-based outdoor learning environment at Ranggo Village Kindergarten in Dompu has provided a comfortable and safe outdoor area according to children's developmental stages. The facilities available in the outdoor learning environment include traditional Dompu games, a ball field, stairs and swings. In addition, the outdoor learning environment has been well organised by the teachers to develop children's motor skills. The use of outdoor facilities is very effective in developing children's gross motor skills. Such as jumping, running, catching the ball and sensor integration skills. Novelty/Originality of this study: Local culture-based outdoor games have a positive effect on improving children's sense of identity, including their ability to improve gross motor skills, coordination and balance, social, cognitive, and self-confidence and courage.